(3JPcQI GdcMGdjfs - (3GdcMGd , Ydj Hf YjSi GdWHjH GdcMGd,J (B400 (3g` s ((3jhSa Hf eMeO Hf jhSa Gdedhi s)
(3ChdgG (B:s
(3hUd GdcJGH CjgG GdCN GdaGVd JSCd Yf LhGeY cJH LGdjfhS ai CeQGV GdYjf hYdGL cd eQV efgG s
(3BNQgG (B:s
(3aEffi GSJYLdJ ai JCdja hLeYg dSQYI MGLJc , aEf cGf Pdc aCUdMg HYO Cf JeYf GdfXQ ajg ,hCf JLYd Ydi ecGaCJi MSf GdOYGA s
(3JSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B49 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs